2012
DOI: 10.1021/nn2021056
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Glutathione Transferase 1 Protects Against Toxicity Induced by Silica Nanoparticles but Not by Zinc Oxide Nanoparticles

Abstract: Microsomal glutathione transferase 1 (MGST1) is an antioxidant enzyme located predominantly in the mitochondrial outer membrane and endoplasmic reticulum and has been shown to protect cells from lipid peroxidation induced by a variety of cytostatic drugs and pro-oxidant stimuli. We hypothesized that MGST1 may also protect against nanomaterial-induced cytotoxicity through a specific effect on lipid peroxidation. We evaluated the induction of cytotoxicity and oxidative stress by TiO2, CeO2, SiO2, and ZnO in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 61 publications
5
66
0
2
Order By: Relevance
“…29 Moreover, different reports have shown that nanoparticle impact is also affected by the presence or absence of a protein coating (or other coatings) on their surface, and that the presence of a corona in serum can mitigate the toxicity of the bare materials. [32][33][34][35][36] In order to further explain and to connect these different outcomes, we have studied how uptake and impact of silica nanoparticles in A549 lung epithelial cells are affected by the presence or the absence of a pre-formed corona in serum. When silica nanoparticles are exposed to cells in serum free conditions, nanoparticle uptake is higher, moreover cellular damage is observed and nanoparticles free in the cytosol can be found.…”
mentioning
confidence: 99%
“…29 Moreover, different reports have shown that nanoparticle impact is also affected by the presence or absence of a protein coating (or other coatings) on their surface, and that the presence of a corona in serum can mitigate the toxicity of the bare materials. [32][33][34][35][36] In order to further explain and to connect these different outcomes, we have studied how uptake and impact of silica nanoparticles in A549 lung epithelial cells are affected by the presence or the absence of a pre-formed corona in serum. When silica nanoparticles are exposed to cells in serum free conditions, nanoparticle uptake is higher, moreover cellular damage is observed and nanoparticles free in the cytosol can be found.…”
mentioning
confidence: 99%
“…В работе [14] Прямой механизм связан с тем, что НЧ могут проникать во внутреннюю среду организма и в клетки, где вызывают генерацию активных форм кислорода (АФК), которые могут вызывать процессы перекисного окисления липидов (ПОЛ) и образование в клетке липоперекисей, которые легко проникают через мембраны, в частности, через мембрану ядра и могут воздействовать на экспрессию генов.…”
Section: Discussionunclassified
“…Таким образом, пероральное введение животным на протяжении 28 дней наночастиц диоксида кремния (размер частиц 10±20 нм) в концентрациях 1, 10, 100 мг/кг массы тела в день влияет на экспрессию отдельных белков микросомальной фракции печени крыс, что согласуется с данными работ, полученными в системах in vitro [6,14] и свидетельствует о возможности оказания этими НЧ системного воздействия на организм при поступлении в желудочно-кишечный тракт. Данное обстоятельство необходимо учитывать в ходе гигиенического нормирования наноструктурированного SiO 2 , применяемого в качестве пищевой добавки.…”
Section: заключение и выводыunclassified
“…However, significant apoptosis did not occur after MNP administration for 24 h based on Hoechst33258 staining results in the present study. The different cellular effects of different nanoparticles may be due to several factors, such as cellular uptake efficiency of nanoparticles, toxicity of the released free ions, and the cell capability for clearing the toxic ions (Singh et al 2010;Sharifi et al 2012;Shi et al 2012). CHOP, also known as growth arrest and DNA damage-inducible gene 153 (GADD153), is an important component of the ER stress-mediated apoptosis pathway (Oyadomari and Mori 2004).…”
Section: Discussionmentioning
confidence: 99%